Early Performance in a Humanistic Medicine Course as a Predictor of Dental Students' Later Clinical Performance. Issue 8 (24th August 2018) - Nelson, Linda Pollak; Maramaldi, Peter; Kinnunen, Taru H.; Kalenderian, Elsbeth
Abstract : The purpose of this study was to test the hypothesis that dental students' early ability to demonstrate a humanistic approach with patients is associated with later clinical performance. A first‐year humanistic medicine course, Patient Doctor I (PDI), at Harvard School of Dental Medicine combines training in conducting the medical interview with human values, placing a high value on strengthening relationships with patients and emphasizing empowerment, respect, and strong communication skills. Retrospective data were collected in the following domains: PDI course evaluations, admissions information, National Board Dental Examination Parts I and II scores, and Promotions Committee and faculty evaluation scores for hand skills and humanistic and interactive patient‐student skills. Planned linear contrasts comparisons were performed for each clinical outcome variable. Tests to support the a priori hypothesis of linear relationships between PDI evaluation ratings and clinical performance, defined as hand skills and humanistic and interactive patient‐student skills scores, were significant, both at p=0.03. This study demonstrated the feasibility of measuring dental students' humanistic qualities during the first year. Humanistic qualities (PDI performance) during the first year were found to be associated with clinical performance in the third year of dental school.